2005
DOI: 10.1159/000088734
|View full text |Cite
|
Sign up to set email alerts
|

Acute Basilar Artery Dissection Treated by Emergency Stenting in a 13-Year-Old Boy

Abstract: We report a 13-year-old boy who presented with acute basilar artery occlusion due to traumatic arterial dissection. Because a grave prognosis was expected if left untreated, and the chance of neurological recovery was believed to be unlikely but not zero, given that emergency stenting for the dissection was performed within 6 h of ictus. Recanalization of the basilar artery with stent placement did not change the poor prognosis in this patient because there was extension of dissection into the posterior cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, the procedure, although technically successful, did not change outcome [2]. In a study of 29 patients with vertebrobasilar dissection, four patients had isolated basilar artery involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the procedure, although technically successful, did not change outcome [2]. In a study of 29 patients with vertebrobasilar dissection, four patients had isolated basilar artery involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Its various possible clinical manifestations range from brain stem ischemia and compression to SAH. Rare cases of spontaneous basilar artery dissection in previously healthy people have been described [2,3]; most cases occur in older patients with basilar artery atherosclerosis [4]. Predisposing factors include trauma, atherosclerosis, hypertension, cystic medial degeneration, fibromuscular dysplasia, syphilis, contraceptive drugs, and migrain [2].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome for childhood BAO following acute intravascular intervention is limited to a small number of published case reports 2,3,8,10–18 . There have been no previous published reports of intravenous thrombolysis for childhood basilar occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no previous published reports of intravenous thrombolysis for childhood basilar occlusion. There have been 13 previously published reports of patients ≤18 years 2,3,8,10–18 who have undergone attempts at basilar artery re‐canalisation through acute intervention with a range from symptom onset to intravascular therapy of less than four hours to three days. We report the case of a 14‐year‐old female with idiopathic basilar thrombosis who successfully underwent mechanical thrombectomy without chemical thrombolysis of a BAO and review the literature on acute interventional therapy for paediatric BAO.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the 35 cases reported in the literature in which there is a somewhat detailed description of the placement of cerebral vascular scaffolds in children, we found that antiplatelet administration for endovascular treatment was extremely variable (On-line Table 2). [2][3][4][5][6][7][8][9][10][11]25,[31][32][33][34][35][36][37][38][39][40][41][42][43] There are neither guidelines published on antiplatelet therapy (APT) in children with cerebrovascular diseases 25 nor conclusive trials on pediatric APT regimens. 44,45 Weight-based dose calculations extrapolated from an adult dosing of 75 mg per day are not only misleading but also may lead to lifethreatening consequences.…”
mentioning
confidence: 99%